Publication Trends of Research on Retinoblastoma During 2001–2021: A 20-Year Bibliometric Analysis - Gu, Xiang; Xie, Minyue; Jia, Renbing; Ge, Shengfang (Frontiers in Medicine, 2021)
Background: Retinoblastoma is the most common primary intraocular malignancy of childhood. Despite high survival and eye salvage as the result of various types of therapies, retinoblastoma remains a disease that places a considerable burden on developing countries. Our study attempted to analyse the research trends in retinoblastoma research and compare contributions from different countries, institutions, journals, and authors. Methods: We extracted all publications concerning retinoblastoma from 2001 to 2021 from the Web of Science database. Microsoft Excel and VOSviewer were employed to collect publication data, analyse publication trends, and visualize relevant results. Results: A total of 1,675 publications with 30,148 citations were identified. The United States contributed the most publications (643) and citations (16,931 times) with the highest H-index value (67) as of February 4, 2021. China ranked second in the number of publications (259), while ranking fourth in both citations (2,632 times) and the H-index (26) ranked fourth. The British Journal of Ophthalmology was the most productive journal concerning retinoblastoma, and Abramson DH had published the most papers in the field. Keywords were categorized into three clusters; tumor-related research, clinical research, and management-related research. The keywords “intravitreal,” “intraarterial,” and “intravenous” appeared the most frequently, with the average appearing year being 2018.1, 2017.7, and 2017.1, respectively. Management-related research has been recognized as a heavily researched topic in the field. Conclusion: We conclude that the United States, China, and India made the most exceptional contributions in the field of retinoblastoma research, while China still has a disparity between the quantity and quality of publications. Management-related research, including intravitreal, intraarterial, and intravenous chemotherapy was considered as a potential focus for future research.